GUIDELINES FOR THE IMPLEMENTATION OF POSYANDU IN THE PANDEMIC TIME COVID-19 AT THE CADRE IN RW 05 AND 06 KELURAHAN SUKAJAYA KECAMATAN TAROGONG KIDUL KAB. GARUT - Ridwan Riadul Jinan; Winasari Dewi; Yusni Ainurrahmah (IKIP SILIWANGI, 2021)
The COVID-19 pandemic has limited space for activities due to the speed of distribution and not yet available drugs, on the other hand, implementing Posyandu is a must even in limited circumstances. Posyandu implementation must use the correct health protocol procedures, however, the knowledge and skills of cadres hamper the implementation of Posyandu. The aim of this PENGMAS is to train cadres in carrying out safe Posyandu activities in accordance with standard health protocols. The PENGMAS method is carried out in three activities, namely socialization, seminars, and Posyandu protocol simulations by measuring cadres' knowledge before and after the activity is carried out to measure the success of this activity. After the activity was carried out, it could be concluded that there was a significant increase in knowledge and understanding from the participants about the implementation of health protocols in the implementation of the Posyandu.